Sistem Pendukung Keputusan Seleksi Ustadz dengan Metode Analitycal Hierarchy Process - Jumhurul Umami (Universitas Darussalam Gontor, 2017)
One of the annual program in Pondok Modern Darussalam Gontor is selection lecturer or chaplain or teacher. In the selection process of teachers who are still there are problems such as the lack of expertise in IT that are still using Microsoft Access displayed manually and not using certain method, besides that just rely on the senior chaplain and part nurture students who are limited in number to evaluate classroom discipline students, the number of candidates for religious teacher will be selected also does not provide maximum results and requires a very long time.Therefore that Gontor require a system that can help in the decision making process to solve these problems, one of them made the Candidate Selection Decision Support System Ustadz Method Using Analytical Hierarchy Process (AHP). The results of the process of this system is the list of 100 best ratings will be a candidate teacher at Pondok Modern Darussalam Gontor I and served for one year to teach.